RELIGIUSITAS KOMUNITAS WARIA DI GORONTALO: Studi Pada Komunitas Binthe Pelangi Kota Gorontalo - Wolinga, Murtin; Caco, Rahmawati; Anwar, Ferlin (TADAYYUN: Journal of Religion, Social and Humanities Studies, 2023)
This paper examines the religiosity of the transgender community in the city of Gorontalo. This type of research is qualitative using a phenomenological approach. The technique used in this research is observation, interview and documentation. The results show that the level of religiosity of transgender life in Gorontalo City is still lacking, seen from the five dimensions of religiosity, namely the religious knowledge, religious practice, religious belief, religious feeling, and religious effect. Of the five dimensions, some are not optimal, such as the lack of religious practice, lack of understanding of religious teachings, lack of experience and practice in worship.